Benturan Kepentingan dalam Manajemen Berita Televisi - Mite Setiansah (Jurnal Komunikasi, 2009)
Television was described as the most important and credible source of news. But, the news is not a neutral product That's why running a news operation so different from any other business. News manager faces some dilemmatic problems. He should make journalistic quality and financial success go hand in hand. This article examines some problems that are faced by television news manager in Indonesia. Attention is given to the conflict of interest of those who finance them.